A nonlinear model of a turbine blade by asymptotic analysis - Rodríguez, José M. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper we obtain a limit model for a turbine blade fixed to a 3D solid. This model is a three-dimensional linear elasticity problem in the 3D part of the piece (the rotor) and a two-dimensional problem (the nonlinear shallow shell equations) in the 2D part (the turbine blade), with junction conditions in the part of the turbine blade fixed to the rotor.
Keywords: asymptotic analysis; nonlinear elasticity; junctions; shallow shells; multistructures